2003
DOI: 10.1161/01.str.0000057814.70180.17
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Granulocyte Colony–Stimulating Factor After Focal Cerebral Ischemia

Abstract: Background and Purpose-The potential neuroprotective effect of the granulocyte colony-stimulating factor (G-CSF) after glutamate-induced excitotoxicity in cell culture and after focal cerebral ischemia in rats was studied. We hypothesized the existence of the G-CSF receptor (G-CSFR) as a main G-CSF effector on neurons, and immunohistochemistry, immunoblotting, and polymerase chain reaction were performed. The G-CSFR-mediated action was studied by activation of signal transducer(s) and activator(s) of transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
311
3
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(335 citation statements)
references
References 36 publications
14
311
3
7
Order By: Relevance
“…Along with other growth factors (Schabitz et al, 2001(Schabitz et al, , 2003, G-CSF has been previously reported to reduce lesion volume after ischemia in mice (Six et al, 2003) and the rat (Schabitz et al, 2003). In these studies, 50 or 60 mg/kg G-CSF was administered via a single subcutaneous injection, and their findings formed the basis for the present study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Along with other growth factors (Schabitz et al, 2001(Schabitz et al, , 2003, G-CSF has been previously reported to reduce lesion volume after ischemia in mice (Six et al, 2003) and the rat (Schabitz et al, 2003). In these studies, 50 or 60 mg/kg G-CSF was administered via a single subcutaneous injection, and their findings formed the basis for the present study.…”
Section: Discussionmentioning
confidence: 91%
“…In vitro studies have shown that G-CSF protects neurons against glutamateinduced neurotoxicity (Schabitz et al, 2003). The main actions of G-CSF are mediated via binding to a G-CSF receptor, present on hematopoietic, neuronal and glial cells (Schabitz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This expression is induced by ischemia, and both counteracts neuronal degeneration and contributes to long-term plasticity after damage. 28,29 Similarly, G-CSF administration after myocardial infarction in mice induces G-CSFR expression in cardiomyocytes and results in the prevention of cardiac remodeling. 30 Regarding the BMC contribution to liver regeneration, our study shows that the number of BM-derived hepatic cells in G-CSF-treated animals was increased up to 6-fold, as compared with the controls.…”
Section: Discussionmentioning
confidence: 99%